2017
DOI: 10.1103/physrevlett.119.140402
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Resource Theory of Quantum Coherence

Abstract: Quantum coherence is an essential feature of quantum mechanics which is responsible for the departure between classical and quantum world. The recently established resource theory of quantum coherence studies possible quantum technological applications of quantum coherence, and limitations which arise if one is lacking the ability to establish superpositions. An important open problem in this context is a simple characterization for incoherent operations, constituted by all possible transformations allowed wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 62 publications
3
100
0
Order By: Relevance
“…The state conversion problem is important in any resource theory, since it determines the value of states for protocols using the resource under study. The result presented here are a significant generalization of recent results on single-shot coherence theory [10,[23][24][25][26] and single-shot resource theories in general [27], and include necessary conditions on the existence of stochastic conversions, which we generalized to higher dimensions.…”
Section: Discussionmentioning
confidence: 52%
“…The state conversion problem is important in any resource theory, since it determines the value of states for protocols using the resource under study. The result presented here are a significant generalization of recent results on single-shot coherence theory [10,[23][24][25][26] and single-shot resource theories in general [27], and include necessary conditions on the existence of stochastic conversions, which we generalized to higher dimensions.…”
Section: Discussionmentioning
confidence: 52%
“…[11]. A relevant subset of IO is constituted by strictly incoherent operations (SIOs), which are completely positive trace-preserving maps whose Kraus operators K i satisfy both [21][22][23][24][25]. We will demonstrate that, although SIO have a very limited coherence distillation power when mixed input states are concerned [17], they nonetheless suffice for our distillation protocol with pure input states.…”
Section: Optimal Distillation Protocolmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35][36][37][38][39] The same is true for its counterpart quantity, [40][41][42] that is, the measurementinduced nonlocality (MIN) which characterizes the global disturbance in a composite state caused by a local nondisturbing measurement on one subsystem. In particular, with the development of the resource theory of quantum coherence, [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] it was shown that the coherence of a system could be converted through incoherent operations into the SQD, instead of the asymmetric QD, of a composite system. [42][43][44][45][46][47][48][49] However, neither the QD nor the MIN of a bipartite system is symmetric in the sense that different results will be obtained (especially for some zero-discord states) if the two subsystems are swapped, which implies that the QD and MIN cannot completely quantify all of the quantum correlations present in a state.…”
Section: Introductionmentioning
confidence: 99%